Age-related asymmetry in left–right ears of sound lateralization with respect to four different rise times - Morita, Kazumoto; Guo, Yijie; Toi, Takeshi (Frontiers in Neuroscience, 2023)
An experimental investigation was conducted to elucidate the auditory characteristics of the older adult population. The study involved 24 older adult and 24 young participants, with the aim of exploring their horizontal lateralization ability. This was achieved by presenting 1-kHz pure tones to the participants’ right and left ears while introducing interaural time differences (ITDs). We examined the impact of four rise times (2, 5, 20, and 50 ms) on the onset of the test sound. The findings revealed that older adult participants exhibited lower levels of lateralization than young participants. Moreover, both older adult and young participants demonstrated diminished recognition of the onset portion as the rise time increased. Of particular significance was the conspicuous presence of a right ear advantage (REA) among young participants as the rise time was extended (statistically significant between the left and right ears at the 1% level, considering an ITD of 0.8 ms and a rise time of 50 ms). In contrast, older adult participants did not exhibit REA, even with a prolonged rise time (not significant at the 5% level at the same condition). These results indicate that the REA is not only present in language, as previously observed, but also extends to a pure tone in young participants. The older adult participants exhibited reduced performance in both left-and right-ear sound recognition. The influence of hearing threshold and preferred ear on sound lateralization performance was minimal. Therefore, it can be inferred that factors other than hearing threshold or preferred ear contribute to the presence of REA in young participants or its decline with age. The central and/or corpus callosum functions may also contribute to this phenomenon.